ANALYSIS THE FACTORS OF PRODUCTION FRESH FRUIT BUNCH (FFB) PALM OIL OF PIR TRANS IN PT MISP SUB-DISTRICT SUBAH THE DISTRICT OF SAMBAS - KOMARIYATI, HERI SANTOSO, NOVIRA KUSRINI, (Jurnal Social Economic of Agriculture, 2018)
PIR TRANS model is The model of community plantation development with partnership system is combine production activities, processing and marketing from one integrated or vertical environmental cooperation system, where large plantations as core with some farmers in plantations as plasma. The problem is farmers From PIR TRANS model to become An independent that can be produced by the production of fresh fruit bunches of oil palm.  The purpose of this study to find out the factors of production fresh fruit bunches palm oil of PIR TRANS in PT MISP sub-district Subah the district of Sambas.     The method used in this research is description method in PT MISP Sub-district Subah the district of Sambas. The data were gained primary data (direct method)  and secondary data (indirect method). This sampling method by using simple random sampling. The amount of sample is taken based on the calculation by using Slovin formula and The number of samples was 53 respondents. The analysis in this research with Cobb-Duoglas regression.     The result of the research shows that the production of fresh fruit bunches oil palm together (simultaneously) by the factors of oil palm production (land area, number of oil palm plantation, labor supply, amount of pesticide, and amount of fertilizer). The factors that affect fresh fruit bunches palm oil in sub-district Subah at 15 year old plant ini partial is land area (m2), and amount of fertilizer (kg). 1% increase of land area will increase fresh fruit bunch production by 0.239% and 1% increase Fertilizer will increase production of fresh fruit bunches of 0,515%.Keywords: Palm Oil, Factors of Production, Fresh Fruit Bunches.